Representations of Finnishness in Sweden - Weckström, Lotta (Studia Fennica Linguistica, 2011)
"More than half a million Swedes - one in twenty - is of Finnish descent. This book explores Finnishness, multilingualism and identities of young people with Finnish background in Sweden. What does it mean to grow up in a Finnish family in Sweden? Who are 'real Finns' and what does it take to be(come) one? Is a shared minority language essential for the survival of the minority, or can a minority culture stay viable without it? What is Finnishness and who, in the end, can define ethnicity? How to make sense of, and how to present interviews that are rich with imitations of accents, jokes and laughter? Representations of Finnishness is Sweden is an ethnographic interview study in the domain of applied language studies. This book is aimed at readers interested in sociolinguistics, linguistic ethnography, and the study of identities. Interviewees' voices take a central position in this book and interview excerpts are used not only as illustrations, but also serve as starting points for discussing broader theoretical concepts. The author, Dr. Lotta Weckström, grew up bilingual - Finnish and Swedish - in Finland. She studied linguistics and migration studies in Germany and the Netherlands, and in this longitudinal study encompasses her expertise."